2008
DOI: 10.1088/0022-3727/41/15/155305
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics analysis and dynamic responses of micro-gas-lubricated journal bearings with a new slip model

Abstract: In this paper, a new slip model based on kinetic theory of gases for gas-lubricated journal bearings in micro-electro-mechanical systems (MEMS) is applied using a physical approach. The corresponding modified governing equation and mathematic model are presented and the flow rate is plotted versus the inverse Knudsen number. Pressure distributions along the gas bearing at various Knudsen numbers and bearing numbers are plotted and the load carrying capacities are also obtained. A numerical analysis of a rigid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…A decrease in the bearing stability is reported through a reduction in the dynamic (stiffness and damping) coefficients, leading to possible rotor contact with the housing in the case of a small axial disturbance. A corresponding study by Zhang et al (2008) reported similar outcomes when using modified slip coefficients in the second-order slip velocity boundary condition.…”
Section: Introductionmentioning
confidence: 61%
“…A decrease in the bearing stability is reported through a reduction in the dynamic (stiffness and damping) coefficients, leading to possible rotor contact with the housing in the case of a small axial disturbance. A corresponding study by Zhang et al (2008) reported similar outcomes when using modified slip coefficients in the second-order slip velocity boundary condition.…”
Section: Introductionmentioning
confidence: 61%
“…Figure 10 shows the three-direction bearing forces, F x , F y , and F z , which vary with eccentric ratios in different flow conditions as per isothermal hydrodynamic analysis. The bearing forces increase with an increase in eccentricity ratio under different flow conditions which has been described in reference (Zhang et al 2008). The action of gas film squeezing becomes significant with an increase in eccentricity ratio, thereby strengthening the bearing forces.…”
Section: Resultsmentioning
confidence: 91%
“…Moreover, the bearing forces under the slip flow region weaken significantly with a high eccentricity ratio. This decrease is because the minimum gas film thickness decreases at this high ratio to strengthen the slip flow (Zhang et al 2008). The bearing forces in the x-and y-direction, F x and F y , are almost similar, but these forces are considerably weaker than z-direction bearing force F z .…”
Section: Resultsmentioning
confidence: 99%
“…But most of these researches are focused on the stability, bifurcation and chaos of the rotating machinery [8,9,11,[17][18][19][20][21][22]. Few discussions are presented for the severity of rub-impact.…”
Section: Impact Energy Model For Rub-impactmentioning
confidence: 99%
“…Zhang et al [7] analyzed the rub-impact fault caused by geometric asymmetry between the rotor and stator, and discussed the grazing phenomenon of the single point rubbing in detail. Zhang and Meng [8][9][10][11][12][13][14][15][16] give a series of researches on the nonlinear Micro-Electro Mechanical Systems (MEMS), including stability, bifurcation and chaos. Also they do a number of detail researches on the influence of several nonlinear parameters to rotor systems.…”
Section: Introductionmentioning
confidence: 99%